Lavender Enterprise / Iliana Moktar ... [et al.] - Moktar, Iliana; Ismail, Haryati; Ibrahim, Nur Irna; Semin, Emilianty; Mohd. Nasir, Merryharyaty (Faculty of Office Management & Technology, 2003)
As a human being, we need food, water, shelter and clothes to fulfill our daily needs. Cloth is very important to us parallel with our growth. Nowadays, there are variety types of fabrics patent in the market, which is the main medium in making a cloth. Based on that, Lavender Enterprise, a partnership company was form to locate the variety types of fabrics patent in the country to convenient our customers in choosing their chosen fabrics. Lavender Enterprise consist 5 persons that holds the following positions; General Manager, Administration Manager. Operation Manager, Marketing Manager and Financial Manager.